The Effects of Implementing Workshop on Radio Broadcasting Class Towards Students Speaking Ability - Wahyuni, Nini (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This research discuss about The Effects of Implementing Workshop on Radio Broadcasting Class Towards Students Speaking Ability.The purposes are to know whether there is improvement in student speaking ability while conducting Workshop on Radio Broadcasting. The participants of this research are English Department students of State Polytechnic of Padang who attend Workshop on Broadcasting course in academic period 2015-2016 .Â The data are collected through class observation, assessment, and questionnaire. The observation data shows that the studentsâ articulation, intonation, and expression in delivering the radio program are become better because they trained to speak clearly and in various way. Meanwhile, the questionnaire data shows that there were 60% students agree that w|Workshop on Radio Broadcasting class is important to improve their speaking ability, 68% students agree that they can improve their grammar, 72% students agree that they can improve their vocabulary, 56% students agree that they can express their idea,Â and their articulation and speaking speed become better, 72% students agree that they can speak more fluent and their accuracy and 60% students agree that by practicing as a radio announcer, news reader and reporter, their self confident is improve. The average score for the studentsâ accent was 2,96, means that they have âForeign accentâ requires concentrated listening, and mispronunciations lead to occasional misunderstandingÂ and apparent errors in grammar or vocabulary. The average score for grammar was 3,08, means that students have frequent errors showing some major pattern uncontrolled and causing occasional irritation and misunderstanding. For vocabulary, the average score was 3,04, means that their choiceÂ of words sometimes in accurate, limitations of vocabulary prevent discussion of some common professional and social topics. For Fluency, the average score was 3,00, means that the speech is frequently hesitant and jerky; sentences may be left uncompleted. Finally, for comprehension, the average score was 3,16, means that they understand careful, somewhat simplified speech when engaged in dialogue, but may require considerable repetition and rephrasing. Even though the improvement on students speaking ability were not significant, it can be concluded that Workshop on Radio Broadcasting class give positive effect in increasing students speaking ability